Toward Firm Performance in Indonesia: The Role of Good Corporate Governance and Investment Opportunity Set - Dedi Rusdi; Indri Kartika; Maya Indriastuti (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2021)
Abstract: This study examined the role of good corporate governance and investment opportunity set in maintaining firm performance. This study's sample population comprised 240 manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2019. The research sample was selected using a purposive sampling method. The data were analyzed by using structural equation modeling analysis (SEM). The results showed that good corporate governance in terms of board size had a negative effect on firm performance. Meanwhile, good corporate governance in terms of board independence and investment opportunity set had a positive effect on firm performance.Keywords: good corporate governance, investment opportunity set, firm performance Menuju Kinerja Perusahaan di Indonesia: Peran Good Corporate Governance dan Investment Opportunity Set Abstrak: Studi ini menguji peran good corporate governance dan investment opportunity set dalam menjaga kinerja perusahaan. Populasi sampel penelitian terdiri dari 240 perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia dari tahun 2016 hingga 2019. Sampel penelitian dipilih dengan menggunakan metode purposive sampling. Analisis data menggunakan analisis structural equation modeling (SEM). Hasil penelitian menunjukkan bahwa good corporate governance ditinjau dari ukuran dewan komisaris berpengaruh negatif terhadap kinerja perusahaan. Sedangkan good corporate governance ditinjau dari independensi dewan komisaris dan investment opportunity set berpengaruh positif terhadap kinerja perusahaan.Kata kunci: good corporate governance, investment opportunity set, kinerja perusahaan